2013
DOI: 10.1177/1078155213510193
|View full text |Cite
|
Sign up to set email alerts
|

The life, death, and attempted rebirth of bevacizumab in breast cancer

Abstract: Breast cancer is the leading cause of cancer in women. In recent years, there has been immense drug discovery and development in the field of breast cancer. Most recently, the role of vascular endothelial growth factor has moved to the treatment forefront with bevacizumab immersed into the literature as well as the media. Bevacizumab, a vascular endothelial growth factor inhibitor FDA approved for the treatment of other cancers, was first studied in metastatic breast cancer. Its use in human epidermal growth f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…The phase 3 trial from 10 countries, with bevacizumab with capecitabine and bevacizumab alone, concluded that the former benefits both progressionfree survival and overall survival in patients with Her2 negative tumours (Gligorov et al, 2014). However, other trials such as (E2100, AVADO, RIBBON-1 and RIBBON-2) showed that this therapy does not improve overall survival of patients with breast cancer (Seddon et al, 2014). Despite this, there may be a benefit with bevacizumab, when the initial MVD is higher since it enhanced vascular normalization.…”
Section: Discussionmentioning
confidence: 99%
“…The phase 3 trial from 10 countries, with bevacizumab with capecitabine and bevacizumab alone, concluded that the former benefits both progressionfree survival and overall survival in patients with Her2 negative tumours (Gligorov et al, 2014). However, other trials such as (E2100, AVADO, RIBBON-1 and RIBBON-2) showed that this therapy does not improve overall survival of patients with breast cancer (Seddon et al, 2014). Despite this, there may be a benefit with bevacizumab, when the initial MVD is higher since it enhanced vascular normalization.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, bevacizumab can induce normalization of newly formed vessels, and thus allow enhanced delivery of chemotherapy to the tumours (Jain, 2005). Furthermore, Avastin has recently been removed as a breast cancer therapy due to adverse effects associated increased cardiovascular toxicity, although this decision is still controversial (Seddon et al, 2014). Thus there is an argument for additional anti-angiogenic therapies displaying reduced adverse effects to anti-VEGF therapy.…”
Section: Tumour Angiogenesismentioning
confidence: 99%